2014
DOI: 10.1016/j.drugalcdep.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, tobacco, and drug use among emergency department patients

Abstract: Background The prevalence of alcohol, tobacco, and other drug (ATOD) use among emergency department (ED) patients is high and many of these patients have unrecognized and unmet substance use treatment needs. Identification of patients in the ED with problem substance use is not routine at this time. Methods We examined screening data, including standardized measures of ATOD use (HSI, AUDIT-C, DAST-10), from 14,866 ED patients in six hospitals across the United States. We expected younger age, male gender, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
(55 reference statements)
3
45
0
2
Order By: Relevance
“…9,13,14,24 Since our medical comorbidity measure combined acute and chronic conditions, it will be important for future work to identify which individual medical conditions (e.g., overdose, injury, respiratory infections, etc.) contribute most strongly to ED admission.…”
Section: Discussionmentioning
confidence: 99%
“…9,13,14,24 Since our medical comorbidity measure combined acute and chronic conditions, it will be important for future work to identify which individual medical conditions (e.g., overdose, injury, respiratory infections, etc.) contribute most strongly to ED admission.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, in agreement with previously published work, ED patients of both sexes also report more tobacco, alcohol, and drug use than previously published national averages. 9,22 …”
Section: Discussionmentioning
confidence: 99%
“…Although this observation is similar to a recent multicenter study, patterns of substance use may vary geographically and our study findings may not be generalizable to other areas of the country. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multi-hospital study across several states, it was found that 45% of adult ED patients were risky alcohol users (Sanjuan, et al 2014); this suggests that the ED may be a prime environment to identify and begin intervening with patients with a spectrum of alcohol use disorders (Brown et al 2012; Field et al 2010; Sommers et al 2013). Studies have investigated the feasibility and efficacy of using behavioral interventions in the ED setting to change drinking and driving behaviors.…”
Section: Introductionmentioning
confidence: 99%